Interaction between serum uric acid and triglycerides in relation to prehypertension in community-dwelling Japanese adults. (February 2014) - Kawamoto, Ryuichi; Tabara, Yasuharu; Kohara, Katsuhiko; Kusunoki, Tomo; Abe, Masanori; Miki, Tetsuro
Abstract There are few data available on the association between serum uric acid (SUA) levels and blood pressure (BP) categories earlier in the disease continuum, when efforts for its prevention may be applicable. We performed a cross-sectional study to examine the association between SUA and prehypertension in a community-dwelling sample of Japanese adults. Study participants without hypertension aged 19 to 90 years [567 men aged 56 ± 15 (mean ± standard deviation) years and 808 women aged 58 ± 13 years] were recruited for a survey at the community based annual medical check-up. The main outcome was the presence of prehypertension [systolic BP (SBP) 120–139 mmHg and/or diastolic BP (DBP) 80–89 mmHg]. After adjustments by gender and age, both SBP (p < 0.001) and DBP (p < 0.001) increased significantly and progressively with increasing SUA and triglycerides (TG) as well as body mass index, LDL cholesterol, and fasting plasma glucose (FPG). Compared to those with normotension, the multivariate-adjusted odds ratio (95% confidence interval) for participants with prehypertension was 1.15 (1.05–1.26) for SUA and 3.19 (1.66–6.14) for TG. The interaction between increased SUA and TG was a significant and independent determinant for SBP (β = −2.474, p = 0.008), but not for DBP (β = −0.608, p = 0.349). Higher SUA levels are associated with prehypertension in participants without hypertriglyceridemia (<150 mg/dL), but not in participants with hypertriglyceridemia (≥150 mg/dL). TG levels may modify the association between SUA and prehypertension.